Shaping the Future of South Africa's Youth Rethinking Post-School Education and Skills Training - Perold, Helene; Cloete, Nico; Papier, Joy (African Minds, 2012)
South Africa has made huge gains in ensuring universal enrolment for children at school, and in restructuring and recapitalising the FET college sector. However, some three million young people are not in education, employment or training and the country faces serious challenges in providing its youth with the pathways and support they need to transition successfully into a differentiated system of post-school education and training. Across nine evidence-based chapters, 17 authors offer a succinct overview of the different facets of post-school provision in South Africa. These include an analysis of the impact of the national qualifications system on occupational training, the impact of youth unemployment, the capacity of the post-school system to absorb larger numbers of young people, the relationship between universities and FET colleges, the need for more strategic public and private investment in skills development, and a youth perspective on education and training policy. The authors have a number of recommendations for improving the alignment between schooling, further education and training, and university education - interventions that could shape the future of South Africa's youth.